2004
DOI: 10.1128/jmbe.v5.73
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of MedMyst : an Internet Teaching Tool for Middle School Microbiology

Abstract: Can web-based technology be used to effectively introduce or reinforce aspects of microbiology to middle school students? This central hypothesis examines whether brief exposure to a web adventure format containing virtual lab experiments and computer games within an engaging story line can impact student learning. An episodic adventure series, MedMyst (http://medmyst.rice.edu), focuses on infectious diseases and the microbes that cause them. The website is not intended to replace classroom instruction, but ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 9 publications
(7 reference statements)
1
15
0
Order By: Relevance
“…No statistically significant differences were found in mean scores for attitudes, satisfaction, usability, and scientific process knowledge, indicating that Disease Defenders does not have a gender bias and is equally effective for males and females in middle school. These results are in line with the finding that both genders benefit from science-based digital games and multi-user virtual environments (1, 8, 13, 14, 20, 21). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No statistically significant differences were found in mean scores for attitudes, satisfaction, usability, and scientific process knowledge, indicating that Disease Defenders does not have a gender bias and is equally effective for males and females in middle school. These results are in line with the finding that both genders benefit from science-based digital games and multi-user virtual environments (1, 8, 13, 14, 20, 21). …”
Section: Discussionsupporting
confidence: 90%
“…Our previous research has demonstrated learning gains in microbiology content among middle and high school students who used MedMyst, an online Flash-based Web adventure series containing virtual lab experiments and arcade-style games set within an engaging mystery story line (http://medmyst.rice.edu/) (20). However, the focus of the three MedMyst missions previously evaluated is on teaching microbiology content and science history, not the scientific process.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers value the power of games to sustain students' focus on specific tasks and to increase motivation and engagement, especially among lower performing students (Millstone, 2012). Previous evaluations conducted by the authors (Bowling, Klisch, & Beier, 2013;Klisch, Miller, Beier, et al, 2012;Miller, Chang, Wang, Beier, & Klisch, 2011;Miller, Moreno, Estrera, & Lane, 2004;Miller et al, 2002Miller et al, , 2006 and research by others (for example, Halpern, Millis, Graesser, Butler, Forsyth, & Cai, 2012;Meluso, Zheng, Spires, & Lester, 2012;Shegog, Lazarus, Murray, Diamond, Sessions, & Zsigmond, 2012;Wu & Pedersen, 2011) have indicated that games are effective tools to promote learning of scientific content in secondary and higher education.…”
Section: Game Development and Instructional Designmentioning
confidence: 99%
“…The company has also collaborated with education specialists to design serious games that teach and motivate STEM (science, technology, education and math) careers. [20][21][22] A common thread is the core belief that designing anything visual-videogames, websites, or physical buildings-is essentially the same act of creation. Common, too, is the disruptive impact new computer tools have had on mature professions.…”
Section: Something Old Something Newmentioning
confidence: 99%